The Impact of Financial Inclusion on the Nigerian Economy - Arthur-Iweze, Ifeanyi Jane (Graduate School of Business (GSB), 2021)
Financial inclusion remains a critical issue for developing economies such as Nigeria, where the focus of the government is to bring all economic units into the pool of the country's financial system. The rate of financial inclusion is an economic yardstick that cannot be discounted and one which remains a clear focal point of different inter-governmental efforts and policy. On one hand, there is the realisation that a low rate of financial inclusion means that a huge percentage of the population rarely has access to the kind of financial services that can take them out of poverty. As a contemporary discourse, this research seeks to assess the impact of financial inclusion on the development of the economy; arguing on the premise that proxy indicators in existing research have failed to provide a clear picture on the impact of financial inclusion on the economy, thereby failing to provide stakeholders with a strong motivation to pursue financial inclusiveness in the country. The focus of the study is to assess the effect of financial inclusion on income inequality and economic growth. To achieve this objective the study leverages on data spanning a period of 34 years (1981 to 2016), based on data generated from the Central Bank of Nigeria Statistical Bulletin and the World Bank Development Indicators. Using the Error Correction Mechanism (ECM),Unit Root Analysis and the Co-Integration analytical framework, the findings indicated that the short and longrun relationship between financial inclusion and economic growth in Nigeria show that the current values of the variables were not significant. Regarding the relationship between financial inclusion and income inequality in Nigeria, the short-run result revealed that only the past values of loans to rural areas and number of commercial bank branches appears to be significant, while at the long-run, the lagged value of gross domestic product per capital, commercial bank deposits and loans to rural areas were found to be statistically significant. The study further notes that financial inclusiveness was a precursor for economic growth in Nigeria. It is on this basis that the study recommends among others that; there is the need to increase loans to the rural areas by at least 50% this can be done through moral suasion to boost the economic activities in the rural areas, improve their aggregate demand, and ultimately their standard of living. There is also the need to engage more workforce in the rural areas to close the inequality gap prevalent in the country.